Deus e criação: a crítica do Livro da Sabedoria à divinização dos astros no estoicismo - Russo, Alexandre Toler (2021)
This PhD thesis is structured around the critique of the divinization of the heavenly bodies found in Sb 13: 1-9. This critique in this part of the Book of Wisdom is a polemic with Stoic philosophy, and this polemic, in our opinion, is properly understood in the ideias of God, creation and in the relation between them in the Book of Wisdom and in Stoicism. For the author of the Book of Wisdom, God transcends its creation, and cannot be identified with it. For this reason, the heavenly bodies, as parts of creation, are not gods, but works of an all-powerful author. For the Stoics, however, God is immanent, pervading materially all his creation. He is also identified with a creative fire situated in one of the spheres of the universe, and the heavenly bodies, localized in this sphere, are made of this fire and can be said to be gods. This difference in the interpretation of God and creation, we think, is the basis of the polemic of the author of the Book of Wisdom with Stoic philosophy with regard to the problem of the divinization of the heavenly bodies